(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In some bacterial infections, the immune system cannot destroy the invading pathogen. In these cases, the invading pathogen is successful in creating a favorable environment for survival and continuation in the host organism. (1) effective violation of the immune response; and (2) protection against immune cells and molecules. S. aureus releases several proteins that contain coagulases and toxins that trigger abscess formation and stagnation. If staphylococcal abscesses are not surgically drained and treated with antibiotics, the spread infection and septicemia will lead to death. In this regard, this document develops a simple mathematical model of abscess formation, which includes characteristics that we consider important for abscess formation. Our goal is to create a mathematical model that reproduces some of the characteristics and behaviors observed in the process of abscess formation. No clinical trials have been conducted to guide the surgeon in the optimal technique of drainage of the Backgroundpilonidal abscess. The purpose of our study was to check whether the location of the incision affects wound healing.